2022
DOI: 10.3390/antiox11050871
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stocking Density on Growth Performance, Antioxidant Status, and Meat Quality of Finisher Broiler Chickens under High Temperature

Abstract: Environmental factors such as stocking density and high temperature can cause oxidative stress and negatively affect the physiological status and meat quality of broiler chickens. Here, we evaluated the effects of heat stress on the growth performance, antioxidant levels, and meat quality of broilers under different stocking densities. A total of 885 28-day-old male broilers (Ross 308) were subjected to five treatments (16, 18, 21, 23, and 26 birds/m2) and exposed to high temperatures (33 °C for 24 h) for 7 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 49 publications
(73 reference statements)
0
17
0
Order By: Relevance
“…As an adaptive mechanism, broilers tend to undergo physiological changes in stressful environments. High-density feeding not only induces oxidative stress, it also impairs the immune and antioxidant systems [50]. In biological systems, oxidative stress is usually caused by an imbalance between antioxidant and pro-oxidative system.…”
Section: Discussionmentioning
confidence: 99%
“…As an adaptive mechanism, broilers tend to undergo physiological changes in stressful environments. High-density feeding not only induces oxidative stress, it also impairs the immune and antioxidant systems [50]. In biological systems, oxidative stress is usually caused by an imbalance between antioxidant and pro-oxidative system.…”
Section: Discussionmentioning
confidence: 99%
“…So that, birds in conventional system gained and converted feed more efficiently than those in new system this may be attributed to higher air speed that pumped directly to birds in new system led to crowded birds. Despite the fact that high HD may reduce airflow at the level of the bird resulting in reduced dissipation of body heat to the air ( Feddes et al, 2002 ; Munonye, 2022 ; Son et al, 2022 ). In addition, May et al (2000) found that broiler chickens exposed to high air velocity consumed more feed and less water while gaining more weight and having a better feed: gain ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Stress can be caused by a variety of environmental factors ( Gangloff and Greenberg, 2023 ). According to recent research, High HD is an important environmental factor and the main constraint in modern poultry production to reach their full growth potential at market age as well as livability, and intestinal health ( Chegini et al, 2019 ; Esmaeili-Fard et al, 2022 ; Franco-Rosselló et al, 2022 ; Son et al, 2022 ). Broilers are typically housed in varying ranges of HD depending on the country's regulations, production system and target body weight, aiming at minimizing fixed costs and maximizing profitability ( Gholami et al, 2020 ; Nawarathne et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…To get the best economic profit, broiler breeders worldwide strive to maximize the weight of chicken produced per square meter of area while minimizing production losses due to high density. The broiler density is now represented as the weight of meat produced rather than the number of birds reared in a square meter of the area [1,2]. Recently, much concern is expressed about the stocking density of broilers in relation Production quantity and quality of broiler and welfare issues such as behavioral and physiological stress .…”
Section: Introductionmentioning
confidence: 99%